Maternal Labor Market Return, Parental Leave Policies, and Gender Inequality in Housework - Pia S. Schober (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This study investigates how the duration of the work interruption and the labor market status of mothers upon their return affect the division of housework in couples after a birth. By observing several parental leave policy reforms in Britain and West-Germany, this research also explores how extended leave entitlements for mothers influence the division of housework. The analysis uses multilevel multiprocess models for 1220 birth events of British couples and 1785 births to German couples based on data from the British Household Panel Survey (1991-2008) and the German Socio-Economic Panel (1985-2009). The results suggest that mothers increase their housework hours with every additional month of employment interruption. Mothers' full-time return seems more effective than a short labor market time-out in altering men's housework contributions and reducing the trend towards a more traditional division of housework. Parental leave policy extensions for mothers were associated with the division of housework only indirectly through their impact on the length of women's work interruptions.
Keywords: 330; Parenthood; parental leave policy; maternal employment; housework; gender division of labor; Britain; Germany; Mütter; Weibliche Arbeitskräfte; Erwerbsverlauf; Elternzeit; Hausarbeit; Geschlecht; Deutschland; Großbritannien